Low-quality flax straw biomass harvesting for subsequent use as fuel: A review - Dudarev, Igor (Lutsk : LNTU, 2022)
Unfavorable conditions for flax growing, harvesting and dew-retting are the reason for the low-quality flax biomass production. This biomass cannot be processed for fiber or other purposes. Therefore, flax straws are burned in the fields or are used as fertilizer by plowing into the soil, which are not good solutions for the environment and subsequent cultivation operations. The limit values of quality properties of fibre flax stem, flax straw and retted straw for their processing are summarized, which can be used to determine the suitability of flax straw biomass for processing or burning. Low-quality flax biomass is inexpensive, ecofriendly and renewable, it can be used as solid fuel for heating greenhouses or buildings located near the field where the flax is grown. Various techniques of fibre flax and oilseed flax harvesting are presented in the article. The technique of low-quality flax harvesting is recommended, which include flax pulling out or flax cutting, flax threshing, flax straw windrow forming, flax straw natural drying on the field in natural way, flax bale forming, flax bale transporting, flax bale burning. This harvesting technology can be used for low-quality fibre flax and oilseed flax. Flax straw biomass can be baled into three bale types: small rectangular bales, big round bales, and big square bales The main requirements for fuel flax biomass bales are recommended. The boiler for burning flax straw bales must be chosen taking into account the shape and size of the bales. For the efficient operation of boilers, it is necessary to take into account the recommended values ​​of bale bulk density and moisture content of flax biomass.
Keywords: flax harvesting; flax biomass; flax straw bale; flax straw burning; solid fuel